2021
DOI: 10.1002/jts.22742
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on treatment‐seeking veterans in the United Kingdom with preexisting mental health difficulties: A longitudinal study

Abstract: Individuals with preexisting psychological difficulties are at risk of further deterioration of their mental well-being during the COVID-19 pandemic. This longitudinal study, conducted during the period between two national lockdowns, aimed to investigate the impact of the COVID-19 pandemic on veterans in the United Kingdom with preexisting mental health difficulties. Treatment-seeking veterans with preexisting mental health difficulties (N = 95) were surveyed in two waves. Wave 1 was conducted at the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Specifically, the clinical and control women and the clinical men (but not the control men) reported an increase in anxiety-related symptoms during COVID relative to before COVID. Increased anxiety symptoms during the pandemic was previously reported in longitudinal studies of community samples ( Huckins et al, 2020 ; Wang, C. et al, 2020 ) and was described as particularly relevant in women ( Gopal et al, 2020 ); however, available findings in clinical samples lacked consistency regarding potential changes in anxiety related to the pandemic ( Hendrikx et al, 2021 ; Tundo et al, 2021 ). Here, by using change scores computed from data collected before the COVID-19 pandemic and during the first lockdown, we underscore higher levels of anxiety symptoms during the pandemic among clinical groups with AUD or HIV and specific difficulties in women.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically, the clinical and control women and the clinical men (but not the control men) reported an increase in anxiety-related symptoms during COVID relative to before COVID. Increased anxiety symptoms during the pandemic was previously reported in longitudinal studies of community samples ( Huckins et al, 2020 ; Wang, C. et al, 2020 ) and was described as particularly relevant in women ( Gopal et al, 2020 ); however, available findings in clinical samples lacked consistency regarding potential changes in anxiety related to the pandemic ( Hendrikx et al, 2021 ; Tundo et al, 2021 ). Here, by using change scores computed from data collected before the COVID-19 pandemic and during the first lockdown, we underscore higher levels of anxiety symptoms during the pandemic among clinical groups with AUD or HIV and specific difficulties in women.…”
Section: Discussionmentioning
confidence: 94%
“…Longitudinal investigations on the impact of the COVID-19 pandemic in individuals with pre-existing neuropsychiatric conditions are emerging. In a study of veterans in the UK (n = 95) with various mental health difficulties, those who experienced more COVID-related stressors were more likely to experience increases in PTSD and common mental health symptoms including anxiety and depression ( Hendrikx et al, 2021 ). Similar results emerged among patients with an Axis-I Anxiety diagnosis, whose symptoms worsened modestly during the early phases of the pandemic ( Tundo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a nationally representative sample of US military veterans, the prevalence of major depressive disorder and PTSD positive screens remained stable while the prevalence of generalized anxiety disorder positive screens increased [ 10 ] and the rate of suicidal ideation decreased nearly 10 months into the pandemic [ 9 ]. Regarding the mental health among treatment-seeking veterans with pre-existing mental health difficulties, the UK study revealed no significant changes in symptoms of PTSD during the pandemic [ 11 ] and a study conducted in Croatia revealed a decrease in PTSD symptoms during the onset of the pandemic as compared to the measurement a year before [ 12 ]. PTSD symptoms and particularly avoidance symptoms may have reduced because of the restrictive measures that prevented greater extent of exposure to reminders of trauma in everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Among veterans with an increased level of mental health suffering, different COVID-related stressors appeared to be the strongest risk factors for increased suicidality [ 9 ], increased distress [ 10 ], common mental disorders, and hazardous drinking [ 32 ]. In treatment-seeking veterans, those who reported more COVID-related stressors and lower levels of social support may have been particularly vulnerable to an increasing severity of a range of mental health difficulties [ 11 , 33 ]. The results of this study indicating no correlation of PTSD symptom level with COVID-related PTE and non-PTE can be explained by a lower potential of COVID-related stressful experiences worsening PTSD symptoms because they differ from the central negative traumatic events (war-related criterion A) [ 12 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation